(untitled) (Interdisciplinary Studies Journal, 2025)
This article investigates the meanings produced by the discourses on an attack from a candidate on another candidate for mayor in the city of São Paulo during a televised debate. The attack involved throwing a chair that candidate José Luiz Datena threw at candidate Pablo Marçal on September 15, 2024, during the transmission of the debate on TV Cultura, in the lead-up to elections which would ultimately choose the mayor of the city with the most significant number of inhabitants in Brazil, São Paulo. With the usage of French historical materialist discourse analysis, we aim to understand the relationship between the discourses that focused on the attack and what are the effects of meaning produced.